Inovasi Dalam Pengelolaan Keuangan, Sarana Dan Prasarana Pendidikan - Rindiani, Natasya; Ismail, Fajri; Afgani, Muhammad Win (Jurnal Ilmiah Wahana Pendidikan, 2025)
Effective and efficient management of education finances, facilities and infrastructure is essential to improving the quality of education. However, many schools still face difficulties in managing education finances, facilities and infrastructure. This study aims to identify innovations in the management of education finance, facilities and infrastructure. In this study the author used descriptive qualitative research, which is research that intends to interpret phenomena that occur and is carried out in various ways involving various existing methods. The results show that innovations in the management of education finance, facilities and infrastructure can improve the quality of education and the efficiency of resource use. Innovations include the use of information technology to manage finances and facilities, curriculum development that is relevant to industry needs, and the use of natural resources to reduce operational costs. This research has implications for the importance of innovation in the management of education finance, facilities and infrastructure to improve the quality of education and the efficient use of resources